The Bahamas : Financial Sector Stability Assessment. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
This article is an overview of the structure of the Bahamian financial system. After the financial crisis in the United States, the Bahamian financial structure showed fragile growth. Tourism, the main source of income for the domestic economy, weakened owing to the U.S. crisis. The increase in oil prices was the key reason for the destroyed infrastructure. However, amidst the vulnerabilities, the banking sector showed stability with high capital and liquidity and sustained challenges; the insurance sector also showed significant improvement. The current financial framework needs to be strengthened, and the mission recommends several reforms to handle financial shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet